Coloration of the testicular peritoneal sheath as a synapomorphy of triatomines (Hemiptera, Reduviidae) - Alevi, Kaio Cesar Chaboli; Oliveira, Jader De; Rosa, João Aristeu da [UNESP]; Oliveira, Maria Tercília Vilela De Azeredo (Instituto Virtual da Biodiversidade | BIOTA - FAPESP, 2014)
Recently, were described some morphological characteristics of 18 species of terrestrial hemipteran grouped in the Alydidae, Coreidae, Corimelaenidae, Lygaeidae, Rhopalidae, Scutelleridae, Tingidae and Reduviidae family that presented found variation in coloration of testicular peritoneal sheath (Reddish, Orange, Yellowish or Transparent). Thus, this study aims to analyzed the coloration of the peritoneal sheath in 44 species of triatomines grouped in nine different genera, with the aim of analyze whether the insects of the Triatominae subfamily also show variations in coloration. By means of analysis of the sheath was possible to observe that members of this subfamily have no interspecific differences, because all species have a transparent sheath. Thus, this paper describes the coloring of the peritoneal sheath in 44 species of the subfamily Triatominae and mainly suggests that the transparent color is one synapomorphy of this important group of insect vectors.

Recentemente, foram descritas algumas características morfológicas de 18 espécies de hemípteros terrestres agrupados nas famílias Alydidae, Coreidae, Corimelaenidae, Lygaeidae, Rhopalidae, Scutelleridae, Tingidae e Reduviidae que apresentaram grandes variações na coloração da bainha peritonial testicular (avermelhada, alaranjada, amarelada ou transparente). Assim, este estudo teve como objetivo analisar a coloração da bainha peritoneal em 44 espécies de triatomíneos agrupadas em nove gêneros diferentes, com o intuito de analisar se os insetos da subfamília Triatominae também apresentam variações na coloração da bainha. Por meio da análise da bainha, foi possível observar que os membros desta subfamília não apresentaram diferenças interespecíficas, pois todas as espécies analisadas possuem bainha transparente. Assim, o presente trabalho descreve a coloração da bainha peritoneal em 44 espécies da subfamília Triatominae e, principalmente, sugere que a cor transparente é uma sinapomorfia deste importante grupo de insetos vetores.
Coloração da bainha peritoneal testicular como uma sinapomorfia dos triatomíneos (Hemiptera, Reduviidae)
Keywords: testículo; Heteroptera; subfamília Triatominae; testicle; Heteroptera; Triatominae subfamily